2015
DOI: 10.3109/17435390.2015.1073396
|View full text |Cite
|
Sign up to set email alerts
|

Male- and female-derived somatic and germ cell-specific toxicity of silver nanoparticles in mouse

Abstract: Silver nanoparticles (AgNPs) are widely used as an antibiotic agent in textiles, wound dressings, medical devices, and appliances such as refrigerators and washing machines. The increasing use of AgNPs has raised concerns about their potential risks to human health. Therefore, this study was aimed to determine the impact of AgNPs in germ cell specific complications in mice. The administration of AgNPs results in toxicity in mice; however, a more detailed understanding of the effects of AgNPs on germ cells rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 46 publications
4
52
0
3
Order By: Relevance
“…As we reported earlier, AgNPs are likely to induce ROS generation in various types of cancer cells, including human breast cancer cells, lung cancer cells, ovarian cancer cells, germ cells, and spermatogonial stem cells. 17,27,28,67,74 A similar phenomenon was also observed in GO-AgNPs-, and DOX-treated SH-SY5Y cells. Lin et al 75 reported that DOX extensively promoted ROS generation in SH-SY5Y cells.…”
Section: Go-agnps Enhance the Generation Of Ros In Sh-sy5y Cellssupporting
confidence: 60%
See 1 more Smart Citation
“…As we reported earlier, AgNPs are likely to induce ROS generation in various types of cancer cells, including human breast cancer cells, lung cancer cells, ovarian cancer cells, germ cells, and spermatogonial stem cells. 17,27,28,67,74 A similar phenomenon was also observed in GO-AgNPs-, and DOX-treated SH-SY5Y cells. Lin et al 75 reported that DOX extensively promoted ROS generation in SH-SY5Y cells.…”
Section: Go-agnps Enhance the Generation Of Ros In Sh-sy5y Cellssupporting
confidence: 60%
“…Previously, several studies have reported that AgNPs have a potential impact on various types of cancer cells, including human lung cancer cells 17,66 and male germ cells. 67 Other studies showed that exposing cells to GO results in the perturbation of the mitochondrial structure and function, as characterized by a decrease in the MMP and the dysregulation of mitochondrial Ca 2+ homeostasis. 68,69 Similarly, nano-sized GO, pristine graphene, and graphene quantum dots caused time-and concentration-dependent decreases in the MMP.…”
Section: Effect Of Go-agnps On Mitochondrial Dysfunctionmentioning
confidence: 99%
“…11 Based on the TUNEL reaction, fluorescence detection of cells with apoptotic DNA strand breaks was performed. To examine total cell numbers, nuclei were labeled simultaneously with DAPI.…”
Section: Terminal Deoxynucleotidyl Transferase Dutp Nick End Labelingmentioning
confidence: 99%
“…3,7,11 Briefly, Escherichia coli were grown in Luria-Bertani broth without NaCl. The flasks were incubated for 21 h in a shaker set at 200 rpm and 37°C.…”
Section: Synthesis and Characterization Of Agnpsmentioning
confidence: 99%
See 1 more Smart Citation